An Evaluation of Stakeholder Involvement in the Development of Communication Plans Used in the Diffusion of Improved Maize Varieties among Farmers in the Semi-Arid Lower Eastern Kenya - Muli, Emily; Sakwa, Maurice; Chakava, Masaya (International Journal of Communication and Public Relation, 2024)
Purpose: While it is acknowledged that increased adoption of agricultural innovations is today hinged on increased and proper application of participatory communication approaches, the adoption of improved maize varieties in the semi-arid Lower Eastern Kenya has remained low at less than 30 percent despite the application of the approach. Proper application of the approach requires adequate involvement of stakeholders in communication activities that include the assessment of the communication needs and the formulation of the communication strategies at all stages of the development and diffusion of an innovation. The purpose of this study was therefore, to assess the level of stakeholder involvement in the development of communication plans used in the diffusion of improved maize varieties among farmers in the semi- arid region of Lower Eastern Kenya Methodology: Qualitative data was collected from farmers, agricultural scientists, agricultural extension officers and documents. It was analysed using a thematic analysis method in accordance with apriori themes and sub-themes developed by the researcher from the literature, principles of participatory communication approaches and the concerns of the research questions. Findings: The study revealed a critical gap in stakeholder involvement during the development of the communication plans which could hinder the formulation of an effective communication strategy. Unique Contribution to Theory, Practice and Policy: In order to improve the adoption rates of improved maize varieties in the semi-arid Lower Eastern Kenya, stakeholders should adequately be involved in the development of communication plans to enable them to uncover their information deficits and identify their existing communication networks necessary for sustained adoption of the maize seeds. This involvement facilitates free and open dialogue which leads to conscientization in which individuals and communities develop a critical understanding of their social reality through reflection and action; ownership where participants accept the initiative and become active participants and; praxis (practice) in which the imitative is fully accepted and used.